Pengaruh Citra Brand Lokal Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada Brand Lokal (Dobujack) - Rahmat Hidayat; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of local brand image and product quality on consumer purchasing decisions on the local brand Dobujack in Bandung City. The method used is a quantitative approach with data collection through questionnaires to 38 respondents from a total population of 800 consumers. The data obtained were tested for validity and reliability before being analyzed using multiple regression. The results of the study indicate that both local brand image and product quality have a significant effect on consumer purchasing decisions, as indicated by a significance value below 0.05 and a calculated F value that far exceeds the F table. This finding emphasizes the importance of synergy between brand image management and product quality in marketing strategies to increase the competitiveness of local brands amidst competition with international brands. This study is expected to be a reference for business actors in formulating effective marketing strategies.